Inter-disciplinary Collaborations Demanded for the Exploration of Applicable Indicators in Abiotic Stress Study-the Case of Tomato - Liu, Minmin; Ouyang, Bo (International Journal of Bio-resource and Stress Management, 2023)
The pace of human population growth will take us beyond 9 billion mark by 2050 while arable land is shrinking, thus food security will be a great challenge in the future. In crop production, one major factor limiting yield is abiotic stress such as drought and salinity, which can reduce the yield by more than 50%. Genetic improvement of crops to various abiotic stresses will be an inevitable road to achieve global food security. Crop tolerances to abiotic stresses are controlled by Quantitative trait loci (QTLs). The various stress indicators like morphological, plant growth, physiological and biological, and molecular play a vital role in assessing the tolerance of genotype to abiotic stresses and has been used in tomato to identify tolerant genotypes. However, intensive collaborations among breeders, botanist, physiologist, molecular biologist, statistician, bioinformatic specialist and other experts are critical for crop abiotic stress research. Breeders are likely to have higher priority in telling which germplasm performs better under stress circumstance and what kind of mechanism might be underlying. In the present scenario, the inter-disciplinary collaborations is demaded for development and execution of fruitful crop improvement programmes to combat the abiotic stresses.